Amnion and Chorion Membranes: Potential Stem Cell Reservoir with Wide Applications in Periodontics - Akanksha Gupta; Suresh D. Kedige; Kanu Jain (International Journal of Biomaterials)
The periodontal therapy usually aims at elimination of disease causing bacteria and resolution of inflammation. It involves either resective or regenerative surgery to resolve the inflammation associated defects. Over the years, several methods have been used for achievement of periodontal regeneration. One of the oldest biomaterials used for scaffolds is the fetal membrane. The amniotic membranes of developing embryo, that is, amnion (innermost lining) and chorion (a layer next to it), have the properties with significant potential uses in dentistry. This paper reviews the properties, mechanism of action, and various applications of these placental membranes in general and specifically in Periodontics.